Integrasi Pendidikan Islam Tradisional Dan Modern Sebagai Basis Pembentukan Islam Moderat di Asia Tenggara - Mahlil; Mukhlis; Nuruzzahri; Marwan; Mukhlis (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2026)
Ideally, Islamic education and local culture in Southeast Asia should work synergistically to foster a moderate Islam that is inclusive, tolerant, and adaptive to social dynamics and globalization. In reality, however, curriculum fragmentation, modernization pressures, and inconsistent practices of moderation persist across Muslim communities. This situation highlights the need to understand how education and culture collectively shape contemporary Islam relevant to the 21st century. This study aims to analyze the integration of traditional and modern Islamic education with local cultural practices as the foundation for fostering moderate Islam in Southeast Asia. It also seeks to contribute theoretically by developing a conceptual framework that connects education, culture, and religious moderation in a holistic manner. The research employs a qualitative approach through library research. Primary data were derived from classical Islamic texts, education curricula, policy documents, and publications of scholars, while secondary data were obtained from academic journals, books, and scientific articles on contemporary Islam. Data analysis was conducted thematically, supported by source triangulation and consistency checks across literature. The findings indicate that the synergy between education and culture enables the internalization of moderation values, shapes an inclusive and adaptive Muslim identity, and provides strategic directions for developing contemporary Islamic education in the 21st century.